A new brackish goby of Drombus (Teleostei: Gobiidae) from Taiwan with short comments on related gobiid species - Chen, I-Shiung; Li, Hsien-En (Zootaxa, 2024)
The brackish environments of Taiwan were relatively unexplored and therefore houses many cryptic fish species, some of which were still unknown to science till this day. After our repeated estuarine surveys and collections, it was encountered an undescribed species of genus Drombus, that can be clearly separated from its congeners by the following unique combinations of characters: (a) dorsal fin elements VI-I, 10; anal fin elements I, 9; pectoral fin elements modally 17; (b) longitudinal scale rows 32–34; transverse scale rows modally 13; predorsal scale rows 9–10; and (c) specific coloration: body brownish with dark red spots scattered; first dorsal fin dusky with a black blotch. The brief morphological comparisons of the new species with its congeners is also provided herein.